Heritability estimates of muscle strength‐related phenotypes: A systematic review and meta‐analysis - Zempo, H.; Miyamoto‐Mikami, E.; Kikuchi, N.; Fuku, N.; Miyachi, M.; Murakami, H. (Scandinavian journal of medicine & science in sports, 2017)
The purpose of this study was to clarify the heritability estimates of human muscle strength‐related phenotypes (H2‐msp). A systematic literature search was conducted using PubMed (through August 22, 2016). Studies reporting the H2‐msp for healthy subjects in a sedentary state were included. Random‐effects models were used to calculate the weighted mean heritability estimates. Moreover, subgroup analyses were performed based on phenotypic categories (eg, grip strength, isotonic strength, jumping ability). Sensitivity analyses were also conducted to investigate potential sources of heterogeneity of H2‐msp, which included age and sex. Twenty‐four articles including 58 measurements were included in the meta‐analysis. The weighted mean H2‐msp for all 58 measurements was 0.52 (95% confidence intervals [CI]: 0.48–0.56), with high heterogeneity (I2=91.0%, P<.001). Subgroup analysis showed that the heritability of isometric grip strength, other isometric strength, isotonic strength, isokinetic strength, jumping ability, and other power measurements was 0.56 (95% CI: 0.46–0.67), 0.49 (0.47–0.52), 0.49 (0.32–0.67), 0.49 (0.37–0.61), 0.55 (0.45–0.65), and 0.51 (0.31–0.70), respectively. The H2‐msp decreased with age (P<.05). In conclusion, our results indicate that the influence of genetic and environmental factors on muscle strength‐related phenotypes is comparable. Moreover, the role of environmental factors increased with age. These findings may contribute toward an understanding of muscle strength‐related phenotypes.